DEVELOPMENT OF PROFESSIONAL SKILLS AND EXPERIENTIAL LEARNING IN A PRACTICAL CONTEXT: CASE STUDY, FIRST-YEAR STUDENTS OF THE AGRONOMY COURSE AT THE INSTITUTO SUPERIOR POLITÉCNICO DO BENGO - Janaína Almeida da Costa, Ariela; Vicente Clemente João, Diogo; Francisco Mungongo Cardoso, Luís (Revista Gênero e Interdisciplinaridade, 2025)
This study analyses the development of professional skills through experiential learning in practical contexts, focusing on first-year Agronomy students at the Instituto Superior Politécnico do Bengo. The research, which is qualitative, descriptive and exploratory, involved 15 students and covered the initial stages of the agricultural cycle: soil preparation, sowing and germination. The findings show that practical activities significantly contributed to consolidating theoretical knowledge, increasing motivation, and developing technical, teamwork and problem-solving skills. Although the study did not include the harvest stage, the data indicate that early practical experiences are essential for the training of future Agronomy professionals.